1) (5х^2 - 3) - (2x + 5) = 5x^2
5х^2 - 3 - 2x - 5 = 5x^25х^2 - 2x - 8 = 5x^2-2x - 8 = 0-2x = 8x = -4
2) x^2 - (x + 1) - (x^2 - 7x + 32) = 3
x^2 - x - 1 - x^2 + 7x - 32 = 3
3) 3(y^3 + 3y - 8) - (5y - y^3 + 7) = 2y^3 - 2y - 15
3y^3 + 9y - 24 - 5y + y^3 - 7 = 2y^3 - 2y - 154y^3 + 4y - 31 = 2y^3 - 2y - 15
2y^3 + 6y - 16 = 0
y^3 + 3y - 8 = 0
The equation is quite complex and may require further simplification to find the exact solutions.
1) (5х^2 - 3) - (2x + 5) = 5x^2
5х^2 - 3 - 2x - 5 = 5x^2
5х^2 - 2x - 8 = 5x^2
-2x - 8 = 0
-2x = 8
x = -4
2) x^2 - (x + 1) - (x^2 - 7x + 32) = 3
x^2 - x - 1 - x^2 + 7x - 32 = 3
x - 33 = 3x = 36x = -36
3) 3(y^3 + 3y - 8) - (5y - y^3 + 7) = 2y^3 - 2y - 15
3y^3 + 9y - 24 - 5y + y^3 - 7 = 2y^3 - 2y - 15
4y^3 + 4y - 31 = 2y^3 - 2y - 15
2y^3 + 6y - 16 = 0
y^3 + 3y - 8 = 0
The equation is quite complex and may require further simplification to find the exact solutions.